1992
DOI: 10.1530/jrf.0.0960699
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of energy substrates in oviductal fluid and blood plasma of pigs during the peri-ovulatory period

Abstract: Summary. Large White gilts, 9 to 18 months old, that had exhibited at least two natural oestrous cycles were divided into three groups (phases): unmated pre-ovulatory, unmated post-ovulatory and mated post-ovulatory (n = 16, 20 and 18). Oviductal luminal fluid samples were collected under anaesthesia by micropipette from the ampulla and ampullary\p=n-\isthmicjunction and analysed by an ultramicrofluorometric technique. Glucose concentrations (mmol l \ m=-\ 1, means combining regions; mean \ m=+-\ sem)were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(65 citation statements)
references
References 26 publications
2
63
0
Order By: Relevance
“…Pyruvate, lactate, lipids and amino acids are present in the oviductal fluid, and the levels of these nutrients fluctuate through the estrous cycle in mice, rabbits, pigs and humans (Nieder & Corder 1982, Nichol et al 1992, Leese et al 1993, Tay et al 1997. The carboxylic acids are processed through immature mitochondria (characterized by the short and less formed cristae, shown in Fig.…”
Section: Nutrientsmentioning
confidence: 99%
“…Pyruvate, lactate, lipids and amino acids are present in the oviductal fluid, and the levels of these nutrients fluctuate through the estrous cycle in mice, rabbits, pigs and humans (Nieder & Corder 1982, Nichol et al 1992, Leese et al 1993, Tay et al 1997. The carboxylic acids are processed through immature mitochondria (characterized by the short and less formed cristae, shown in Fig.…”
Section: Nutrientsmentioning
confidence: 99%
“…The concentrations of glucose in the oviduct fluid, which differ substantially among mammals, have been shown to increase during the preovulatory period of the estrous cycle (Vecchio et al 2010). In pigs, Nichol et al (1992) reported that the concentrations of glucose were significantly lower in the whole oviduct (0.59 mM) than in the blood plasma (4.56 mM), but its concentration in the ampullary-isthmic junction during the preovulatory period (1.65 mM) was greater than during other periods of the estrous cycle. In boar sperm, the utilization of glucose is controlled in part by the heterogeneous localization of GLUT family transporters over the entire sperm surface (Bucci et al 2010).…”
Section: Role Of Aldose Reductase In Sperm Capacitationmentioning
confidence: 99%
“…Furthermore, as detected by electron probe analysis in rodents, there are differences in elemental composition between ampullary and isthmic fluid [18]. Using a surgical approach to regional fluid sampling, a series of differing environments was detected along the duct [19]. Bearing in mind the contractile activity of the myosalpinx, accentuated during the period of oestrus and close to ovulation, a mixing of fluids might have been anticipated, rendering the composition more or less homogeneous.…”
Section: Fluid Microenvironmentsmentioning
confidence: 99%